Tiktok como herramienta de comunicacion de moda: El caso Zara - Cristófol-Rodríguez, María del Carmen; Carrasco-Santos, María Jesús (GKA Ediciones, 2023)
The visual and interactive content that TikTok allows makes it a perfect ally for fashion brands. This study aims to analyse how Zara uses TikTok as a digital communication tool through three objectives: the evaluation of trends, the influence of Zara's communication strategy on TikTok and the identification of the degree of engagement that the user has with the brand. The results show that Zara makes a great communicative effort, creates strategic content and the degree of engagement generated between the brand and its public is solid.
Tiktok as a fashion communication tool: The Zara case
Keywords: Redes sociales en Internet; Moda - Publicidad; Zara; TikTok; Social Media; Fashion communication; Internet